Desert heat : a Brady novel of suspense - Jance, Judith A., 1944- (Joanna Brady ;, 2009)
Life is good for Joanna Brady in the small desert community of Bisbee.She has Jenny, her adored nine-year-old daughter, and solid, honest, and loving husband, Andy, a local lawman who's running for Sheriff of Cochise County.But her good life explodes when a bullet destroys Andy Brady's future and leaves him dying beneath the blistering Arizona sun.